Generation of vessel co-option lung metastases mouse models for single-cell isolation of metastases-derived cells and endothelial cells - Anne Cuypers; Laure-Anne Teuwen; Victoria L. Bridgeman; Laura P.M.H. de Rooij; Guy Eelen; Mieke Dewerchin; Anna Rita Cantelmo; Joanna Kalucka; Ann Bouché; Stefan Vinckier; An Carton; Ann Manderveld; et al. (STAR Protocols, 2022)
Summary: Tumor vessel co-option, a process in which cancer cells “hijack” pre-existing blood vessels to grow and invade healthy tissue, is poorly understood but is a proposed resistance mechanism against anti-angiogenic therapy (AAT). Here, we describe protocols for establishing murine renal (RENCA) and breast (4T1) cancer lung vessel co-option metastases models. Moreover, we outline a reproducible protocol for single-cell isolation from murine lung metastases using magnetic-activated cell sorting as well as immunohistochemical stainings to distinguish vessel co-option from angiogenesis.For complete details on the use and execution of this protocol, please refer to Teuwen et al. (2021). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.